Consumer Protection in Cross-Border E-Commerce Transactions in the Era of Digital Trade - Gunardi Lie; Angela Olivia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has significantly transformed international trade activities, particularly through cross-border e-commerce platforms that are increasingly accessible to the public. This condition provides consumers with efficient access to obtain products from various countries without geographical barriers. On the other hand, such convenience also gives rise to various legal issues, especially in relation to consumer protection in international trade transactions. Differences in legal systems, jurisdictions, and dispute resolution mechanisms pose significant challenges in ensuring the fulfillment of consumer rights. This research aims to analyze legal protection for consumers in cross-border e-commerce transactions and to identify the challenges in its implementations. The research employs a normative-juridical method with a statutory and literature approach. The results indicate that consumer protection in international e-commerce transactions still faces various obstacles, primarily due to differences in regulations among countries and limitations in law enforcement. Therefore, regulatory harmonization and enhanced international cooperation are necessary to establish effective consumer protection and ensure legal certainty in cross-border transactions.